Effects of physical fitness on mental health of Chinese college students: across-sectional study - Ma, Shuzhen; Yang, Yang; Soh, Kim Geok; Tan, Hermione (BioMed Central, 2024)
Background The physical and mental health of college students is often mentioned, but there is limited research on a direct relationship between the mental health status of college students and their physical fitness level. This study mainly proves the relationship between Chinese college students’ mental health and physical fitness indicators.